Pengurangan Zat Warna Remazol Red Rb Menggunakan Metode Elektrokoagulasi Secara Batch - Novie Putri Setianingrum; Agus Prasetya; Sarto Sarto (Jurnal Rekayasa Proses, 2017)
Batik is one of the distinctive cultural chacteristic of the Indonesian national that has gained recognition from UNESCO. Batik industries have grown rapidly. However, the activity  industry produces liquid, especially from batik’s dyeing processes.. The conventional method which is used for processing wastewater still has limitation so that an innovation method wastewater treatment is need for example electrocoagulation. Electrocoagulation is  a process of coagulation using unidirectional electrics current through electro-chemical process. In this work, electrocoagulation was employed to treat wastewater (synthetic dyes remazol red (Rb) as wastewater model). The method was carried out by varying the distance between electrode distance and electrical voltage. Variation of distance between electrode range were  2 cm and 3 cm while variation of electrical voltage range were 10 volt and 15 volt. To determine the effect of electrode distance and electrical voltage on treatsment performances the chemical oxygen demand(COD), total suspended solid (TSS) and waste color. The samples were taken at 10 minutes, 20 minutes, 40 minutes and 60 minutes during the process. The results showed that the distance of the electrode and the voltage affected  to thr reduction of COD, TSS and waste color. The optimum elecrode distance and voltage in this research were 2 cm and 10 volt. The research showed the decrease in COD concentration from 428 mg/L to 54 mg/L, TSS concentration from 850 mg/L to 277 mg/L and the decrease in waste color from 2733 PtCo to 75,5 PtCo. ABSTRAKBatik merupakan salah satu ciri budaya khas bangsa Indonesia yang telah mendapatkan pengakuan dari UNESCO. Industri batik mengalami pertumbuhan cukup pesat. Aktivitas produksi dalam industri semakin meningkat menyebabkan limbah cair terutama dari proses pewarnaan semakin banyak. Metode konvensional untuk pengolahan limbah cair masih memiliki kekurangan sehingga memerluka metode pengolahan limbah alternatif, yaitu metode elektrokoagulasi. Proses elektrokoagulasi merupakan suatu proses koagulasi  dengan menggunakan arus listrik searah melalui proses elektrokimia. Proses elektrokoagulasi dilakukan dengan memvariasikan tegangan listrik dan jarak antar elektroda yaitu 10 volt dan 15 volt serta 2 cm dan 3 cm. Untuk mengetahui pengaruh tegangan listrik dan jarak antar elektroda maka dilakukan pengukuran COD, TSS dan Warna dimana sampel diambil setiap 10 menit, 20 menit, 40 menit dan 60 menit lalu dianalisis. Hasil penelitian menunjukkan bahwa tegangan listrik dan jarak antar elektroda memberikan pengaruh terhadap penurunan COD, TSS dan Warna pada limbah cair sintetis Remazol Red RB. Jarak antar elektroda dan tegangan listrik yang optimum pada penelitian ini yaitu 2 cm dan 10 volt dengan penurunan konsentrasi COD yang pada awalnya 428 mg/L menjadi 54 mg/L, penurunan TSS yang pada awalnya 850 mg/L menjadi 277 mg/L dan penurunan Warna yang pada awalnya sebesar 2733 PtCo menjadi 75,5 PtCo.